2022
DOI: 10.1017/s0008197322000241
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Vaccine Inequity During the Covid-19 Pandemic: The Trips Intellectual Property Waiver Proposal and Beyond

Abstract: This article examines global vaccine inequity during the COVID-19 pandemic. We critique intellectual property (IP) law under the 1994 WTO TRIPS Agreement, and specifically, the role that IP has played in enabling the inequities of production, distribution and pricing in the COVID-19 vaccine context. Given the failure of international response mechanisms, including COVAX and C-TAP, to address vaccine inequity, we argue the TRIPS waiver proposal should be viewed as offering a necessary and proportionate legal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The estimates suggested that BioNTech, the biotechnology company behind Pfizer's mRNA vaccine, alone could boost Germany's gross domestic product (GDP) by 0.5% in 2021 ( 35 ). Nonetheless, in 2022, the USA offered support to the TRIPS waiver with the key limitation that the waiver be issued to the production of vaccines only, not therapeutics and diagnostics ( 36 ). To achieve global vaccine equity, a nationalistic approach based on the welfare of the global community must be prioritized over private profits.…”
Section: Resultsmentioning
confidence: 99%
“…The estimates suggested that BioNTech, the biotechnology company behind Pfizer's mRNA vaccine, alone could boost Germany's gross domestic product (GDP) by 0.5% in 2021 ( 35 ). Nonetheless, in 2022, the USA offered support to the TRIPS waiver with the key limitation that the waiver be issued to the production of vaccines only, not therapeutics and diagnostics ( 36 ). To achieve global vaccine equity, a nationalistic approach based on the welfare of the global community must be prioritized over private profits.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic has brought several lessons regarding the effects of monopoly on access inequity to health technologies ( 8 ). One lesson from the COVID-19 pandemic is that the monopoly situation not only affects prices but also the supply in a health emergency ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, almost US$ 1 billion of US taxpayers was invested in the Moderna vaccine R&D process ( 7 ). However, those investments were not followed with a commitment to ensure equitable global access ( 8 ). The inequitable distribution of COVID-19 vaccines was considered by the World Health Organization (WHO) “a moral and global security failure with health and economic consequences” ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVAX was created during COVID-19 to facilitate vaccine equity, acting as the key purchasing agent for the world, pooling demand, and exercising significant market shaping and equitable allocation powers. However, as COVAX failed by some margin to meet its distribution goals, 14 countries like South Africa and India railed against treating intellectual property (IP) rights as “sacrosanct” 15 — seeking with limited success to relax the application of the World Trade Organization (WTO) Agreement on the Trade Related Aspects of Intellectual Property (TRIPS Agreement). There remain systemic barriers to LMICs in manufacturing their own medical countermeasures during a pandemic, and without significant changes to these systemic barriers, they will remain reliant on pooling and distribution mechanisms facilitated by the WHO and other international organizations.…”
Section: Calls For Abs In the Pandemic Treatymentioning
confidence: 99%